Concerns about Data Integrity of 22 Randomized Controlled Trials in Women's Health - Liu, Yizhen; Thornton, Jim G.; Li, Wentao; van Wely, Madelon; Mol, Ben W. (American Journal of Perinatology, 2021)
Objective During a review on postpartum hemorrhage, we identified randomized controlled trials (RCTs) of one author conducted at the same time and place for the same condition, with large differences in baseline characteristics. We assessed the data integrity of the RCTs of this author.Study Design We undertook a focused analysis of the data integrity of all RCTs published by Dr. Ahmed M. Maged. We examined the studies for clinical logic and made pairwise comparisons of baseline characteristics and outcomes between trials. We used mathematical methods to assess whether the distribution of baseline characteristics was compatible with chance.Results Between March 2015 and December 2019, Dr. Maged published 22 RCTs (n = 3,722). The median number of participants randomized per center per month was 32 (range = 1–89). Fifteen studies were either not or retrospectively registered, with one study registered 1 year after publication. One study was submitted for publication prior to the completion of the described study period. There were many unusual findings in the studies, including biologically implausible occurrences such as the absence of an association between gestational age and birthweight in seven studies and very different body mass index between three trials, which ran at the same time in the same hospital on the same topic as well as unlikely occurrences such as limited participant drop outs. One paper contained considerable text duplication and identical data to that in a paper published by a different author group from a different hospital, with both papers submitted at the same time. Mathematical analysis of the baseline characteristics of all 22 trials indicated that at least some of the reported baseline characteristics were unlikely to be the result of proper randomization.Conclusion Our analyses of the 22 RCTs of Dr. Maged suggest potential data integrity issues in at least some of them. We suggest that journals investigate according to the Committee on Publication Ethics guidelines. The procedures demonstrated in this paper may help to assess data integrity in future attempts to verify the authenticity of published RCTs.Key Points
Keywords: data integrity; research integrity; Monte Carlo simulation; randomized control trials